Recent progress of rare earth doped hydroxyapatite nanoparticles: Luminescence properties, synthesis and biomedical applications - Gu, Mengqin; Li, Wei; Jiang, Li; Li, Xiyu (Acta biomaterialia, 2022)
Hydroxyapatite nanoparticles (HAP NPs) are host materials and can be modified with various substrates and dopants. Among them, rare earth (RE) ions doped HAP NPs have gathered attention due to their unique physicochemical and imaging properties. Compared to other fluorescence probes, RE-doped HAP NPs display advantages in high brightness, high contrast, photostability, nonblinking, and narrow emission bands. Meanwhile, their intrinsic features (composition, morphology, size, crystallinity, and luminescence intensity) can be adjusted by changing the dopant ratio, synthesizing temperature, reaction time, and techniques. And they have been used in various biomedical applications, including imaging probe, drug delivery, bone tissue engineering, and antibacterial studies. This review surveys the luminescent properties, fluorescence enhancement, synthetic methods, and biocompatibility of various RE-doped HAP NPs consolidated from different research works, for their employments in biomedical applications. For this literature review, an electronic search was conducted in the Pubmed, Web of Science, Google Scholar, Scopus and SciFinder databases, using the keywords: hydroxyapatite, rare earth, lanthanide, fluorescence, and imaging. Literature searches of English-language publications from 1979 with updates through April, 2022, and a total of 472 potential papers were identified. In addition, a few references were located by noting their citation in other studies reviewed. Hydroxyapatite nanoparticles (HAP NPs) have a broad range of promising biological applications. Although prospective biomedical applications are not limited to rare earth-doped hydroxyapatite nanoparticles (RE-doped HAP NPs), some cases do make use of the distinctive features of RE-elements to achieve the expected functions for HAP families. This review surveys the luminescent properties, synthetic methods, and biocompatibility of various RE-doped HAP NPs consolidated from different research works, for their employments in biomedical applications, including imaging probe, drug delivery, bone tissue repair and tracking, and anti-bacteria. Overall, we expect to shed some light on broadening the research and application of RE-doped HAP NPs in biomedical field. [Display omitted]